Biochemical Evaluation of Garden-Strawberry Berries When Using Foliar Top-Dressing - Mistratova , Natalia; Savinich, Elena; Samarokova, Anna (KnE Life Sciences, 2021)
This study examined the use of foliar treatment with solutions of macroand microelements when growing garden strawberries of the varieties Elista, Pervoklassnitsa, Zephyr, and Solnechnaya Polyanka in the conditions of the Krasnoyarsk forest. The agrochemical background of the soil when planting garden strawberry bushes in the open ground indicated its high fertility in terms of a set of indicators. At the same time, there was a shortage of micronutrient elements in the soil at the experimental site: Cd (0.2 mg/kg), Cu (0.5 mg/kg), Zn (1.3 mg/kg), Co (0.6 mg/kg) and Cr (0.3 mg/kg). Availability of manganese (65.4 mg/kg) and lead (2.0 mg/kg) was average. The Elista variety was distinguished in the control version of the experiment in the accumulation of copper in the berries (0.9 mg/kg). After foliar treatments with Cu 1% + 8 microelements, the highest Cu content was observed in the berries of the Solnechnaya Polyanka (1.1 mg/kg) and Pervoklassnitsa (1.0 mg/kg) varieties. The Zephyr variety had the lowest copper content in its berries: 0.4 mg/kg. The control variant of the Zephyr variety was distinguished in its iron content (4.6 m/ kg). After foliar treatments with Fe 2% + 8 micronutrient elements, the maximum amount of iron in the berries was recorded in the Solnechnaya Polyanka variety: 4.4 mg/kg. The Elista and Zephyr varieties had a rich biochemical composition without treatment with micronutrient elements. The Pervoklassnitsa and Solnechnaya Polyanka varieties were responsive to foliar feeding with micronutrient elements. Keywords: Strawberries, non-root top-dressing, biochemical composition of berries